When Eagles Fall - Casanova, Mary (Book collections on Project MUSE., 2014)
Things have not been easy for thirteen-year-old Alex lately. Recent events have taken their toll on her family, and when drinking at a party lands her in the hospital, things only get worse. Her mother decides to send her away to spend the summer working with her father, an esteemed eagle researcher, on the wild and remote shores of Rainy Lake in Minnesota. The bugs, the outhouse, the isolation-it's a whole different world from her home in California. The hardest part of Alex's exile is dealing with her father who is sure that he knows it all. When he chooses not to save a pair.